ANALISA KEPUASAN MASYARAKAT DALAM KOMUNIKASI PARIWISATA TERHADAP WISATA DANAU TOBA BUKIT SIMARJARUNJUNG, KABUPATEN SIMALUNGUN - Irene Silviani; Nazlah Rachma Panggabean (Jurnal Ranah Komunikasi, 2020)
This study analyzed tourism communications related to community satisfaction in tourism services, quality of products, and the attraction of Lake Toba. Quantitative descriptive research using non probability and purposive sampling involving 100 respondents. The results showed that the majority of respondents were women as many as 58%. While for men 42%. Thus women are more likely to like Lake Toba tourism. Based on the simple linear regression equation, it is known that Y = 12.691 + 0.736X, which means that every 1% addition of the level of community satisfaction (X) will increase Lake Toba tourism by +0.736. While the comparison of the t value and t table, it is known that the t value of 28.600 is greater than the t table of 1.98447, so it is concluded that H0 is rejected and Ha is accepted, that community satisfaction influenced on Lake Toba Tourism. The magnitude of the influence of community satisfaction on Lake Toba Tourism is obtained from the SPSS output with an R Square value of 0.893. This means that the effect of community satisfaction on Lake Toba Tourism is 89.3%, while 10.7% is influenced by variables are not in this study